Accountability: Uma análise sobre as práticas de governança em uma universidade federal brasileira - Colombo, Paulo Keese (2022)
With the advent of the New Public Management movement, which promoted changes in the management models adopted in public institutions in Brazil, the principles of accountability, understood as a response by government managers in order to be accountable to society, end up gaining relevance within the public institutions of higher education. Thus, this work aims to verify how an institution of higher education promotes accountability within the areas of accountability, transparency and accountability, these heard as the major subsystems that make up accountability. For this, the documental analysis of the Institution's Annual Management Report and the Corregedoria's Biannual Report were used as data collection techniques, and the interview with the managers responsible for the preparation of these documents. The material collected from the applied techniques was categorized within the three accountability subsystems listed, giving room for interpretations regarding the degree of accountability promotion in its different interfaces. In short, this work provided greater knowledge about the areas that involve the promotion of accountability, pointing to possible improvements in order to improve the efficiency and relevance of the educational role of the university in the country.